Legal Protection for Victims of Human Trafficking in Indonesia - Aida Dewi (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2026)
This study discusses legal protection for victims of human trafficking in Indonesia. There is a new mode of online human trafficking through social media that ensnares Indonesian workers in the form of fictitious job offers that lead to forced labor exploitation in the realm of online fraud or online scamming. This study uses a normative legal research method with a legislative approach and conceptual approach. The results of the study show that human trafficking crimes in involving Indonesian workers as victims have fulfilled the elements of a criminal offense under Article 2 of Law No. 21 of 2007 concerning the Eradication of Trafficking Crimes and violate the Palermo Protocol as well as the principles of the International Labor Organization (ILO) in ILO Convention No. 29 concerning forced labor and Convention No. 105 concerning the Abolition of Forced Labor. Regarding law enforcement and protection, there are obstacles in the form of weak law enforcement capacity, overlapping regulations, lack of budget, and minimal coordination between agencies. Keywords: Legal Protection; Victims; Human Trafficking